Variation in the morphology and effector profiles of Exserohilum turcicum isolates associated with the Northern Corn Leaf Blight of maize in Nigeria - Bankole, F.; Badu-Apraku, B.; Salami, A.O.; Falade, Titilayo D.O.; Bandyopadhyay, R.; Ortega-Beltran, A. (Springer, 2023)
Background Maize production in lowland agro-ecologies in West and Central Africa is constrained by the fungus Exserohilum turcicum, causal agent of Northern Corn Leaf Blight (NCLB). Breeding for resistance to NCLB is considered the most effective management strategy. The strategy would be even more effective if there is adequate knowledge of the characteristics of E. turcicum in a target region. Maize leaves showing NCLB symptoms were collected during field surveys in three major maize growing areas in Nigeria: Ikenne, Ile-Ife, and Zaria during 2018/2019 and 2019/2020 growing seasons to characterize E. turcicum populations interacting with maize using morphological and molecular criteria.